KAJIAN PEMBERDAYAAN MASYARAKAT MELALUI DESA SIAGA DALAM RANGKA UPAYA PENURUNAN AKI DI BERGAS KABUPATEN SEMARANG - Sandy Isna Maharani; Listyaning Eko Martanti; Bahiyatun Bahiyatun; Rifa'tun Nisa (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2018)
Background: Increasing maternal and child health status is one of Millenium Developement Goals (MDGs) that targetted to be reached in 2015. Indonesia has the highest Maternal Mortality Rate (MMR) compared to other ASEAN countries. Based on SDKI data, MMR in Indonesia increased significantly to be 359 per 100,000 live births in 2012. Meanwhile, in the same time,MMR in Semarang City is 80.6 per 100,000 live births and the highest maternal mortality casesoccured in the working area of Bergas Public Health Center as much as 3 cases. The aim of this study is to determine how community empowerment through Desa Siaga could reduce MMR in the working area of Bergas Public Health Center. Methods: The method of this study is qualitative research by using triangulation data that obtained from depth interview, oberservation and secondary data collection. Data was analyzed by using content analysis method